Application of the Principle of Legality in the Criminal Justice System: Ensuring Justice and Protection of Human Rights - Hartoyo; Noenik Soekorini; Nur Handayati (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This article aims to find out about the application of the legality principle in the criminal justice system. Legality is a legal principle that states that there is no criminal act without a clear legal basis. The research method used in this study is a literature study with a normative analysis approach to analyze and interpret laws and regulations related to the principle of legality in the criminal justice system, case studies, and analyzed through comparative studies. Based on the research results, it can be concluded that the principle of legality has a crucial role in ensuring justice and protecting human rights in the criminal justice system. Although there are several challenges in applying this principle, efforts to strengthen adherence to the legality principle must be continued through training, supervision, and evaluation of criminal law policies. In the study of literature and normative analysis, it was found that the principle of legality has a strong legal basis and is the main basis for forming criminal law policies.